KNOWLEDGE LEVEL AND ATTITUDE OF PATIENTS FRACTURE THAT CHOOSE TRADITIONAL TREATMENT (Bone Setter) BEFORE TREATING TO POLYCLINIC ORTHOPAEDIC AND TRAUMATOLOGIC AT UNDATA GENERAL REGION HOSPITAL PALU PERIOD OF NOVEMBER-DECEMBER 2016 - Wulandari, Hanif Iga; Munir, Muhammad Ardi; Hutasoit, Gina Andyka (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background: In most cases neglected fracture occurs in people who are educated and under socioeconomic status. In addition to using health centers by medical personnel, not a few people are more confident in traditional medicine, so a few patients with fractures who came to the hospital are already experiencing complications due to first treatment is not appropriate, in accordance with the principles of correct bone treatment. The classic reason that delays patients with fracture was to the hospital is an economic factor.Methods: This study design is carried out by using an observational study design. The sampling technique in this research is intentional sampling consisting of 64 respondents. Data collection through questionnaires.Result: From the 64 samples studied, the results of the level of knowledge about bone fractures in the good categories 11 respondents, enough category 41 respondents, less category 12 respondents, and the attitude of the patient fracture for the treatment of the fractures in good category 41 respondents, enough category 7 respondents, and less category 16 respondentsConclusion: Based on the level of knowledge and attitude of fractures in traditional medical research carried out by the patient before treatment in the clinical orthopedic surgery hospital Undata has the result of the level of knowledge (know) enough and a Positive attitude towards an initial treatment of fractures. Keywords: Knowledge level, Attitude, Fracture Latar Belakang: Pada umumnya neglected fracture terjadi pada orang yang berpendidikan dan berstatus sosio-ekonomi rendah. Selain memanfaatkan fasilitas pelayanan kesehatan oleh tenaga medis, tidak sedikit masyarakat yang lebih percaya kepada pengobatan tradisional, sehingga tidak sedikit pula pasien patah tulang yang berobat ke Rumah Sakit pada saat datang sudah mengalami komplikasi akibat penanganan pertamanya yang tidak baik atau tidak sesuai dengan prinsip penanganan patah tulang yang benar. Adapun alasan klasik pasien patah tulang yang terlambat berobat ke Rumah Sakit adalah faktor ekonomi.Metode: Jenis rancangan penelitian ini dilakukan dengan menggunakan desain penelitian observasional deskriptif. Teknik pengambilan sampel dalam penelitian ini adalah Purposive Sampling yang terdiri dari 64 orang responden. Pengumpulan data dengan menggunakan kuisioner.Hasil: Berdasarkan 64 sampel yang diteliti, hasil tingkat pengetahuan responden tentang patah tulang pada kategori baik 11 responden, cukup 41 responden, kurang 12 responden, dan sikap pasien fraktur terhadap penanganan patah tulang kategori baik 41 responden, cukup 7 responden, dan kurang 16 responden.  Kesimpulan: Berdasarkan penelitian yang dilakukan tingkat pengetahuan dan sikap pasien fraktur yang berobat di pengobatan tradisional sebelum berobat di poliklinik bedah tulang RSUD Undata memiliki hasil tingkat pengetahuan (Know) cukup dan sikap yang positif terhadap penanganan awal patah tulang. Kata Kunci: Tingkat Pengetahuan, Sikap, Fraktur